Lectura y reinterpretación contemporánea de las máscaras de tigua aplicado a productos textiles - Catota Ipiales, Juan Carlos (2016)
This Project that will be presented, is development in Tigua Community in Cotopaxi Province, Latacunga Canton, here the equipment found a big problem, and it was necessary to resolve through an investigation. For this reason, we start an investigative process where the main aspect was focus in the wood masks that are elaborated in artisanal methods in this Community, these ones are so amazing but they are not recognized as the pictures are, in this case the researching group take in account a proposal named: “CONTEMPORANEOUS TIGUA MASKS IN READING AND REINTERPRETATION APPLIED IN CLOTHS PRODUCTS”. This researching was development to have values the culture and traditions in the province and the country, doing the tools and knowledge use with the support to the Graphic Design career.